Complementary Reactivity of 1,6-Enynes with All-Metal Aromatic Trinuclear Complexes and Carboxylic Acids - Cecchini, Chiara; Lanzi, Matteo; Cera, Gianpiero; Malacria, Max; Maestri, Giovanni (Synthesis, 2019)
The distinct reactivity of 1,6-enynes in the presence of a trinuclear metal complex activated by a carboxylic acid is presented. The triplatinum catalyst enables the cyclization of the substrate and subsequent incorporation of a nucleophile in the final product. In contrast, sequential cyclization/double bond shift occurs under analogous conditions in the presence of the corresponding tripalladium complex.
Keywords: enynes; palladium; platinum; clusters; aromaticity; cyclization